Effect of a novel pedal design on maximal power output and mechanical efficiency in well-trained cyclists - Koninckx, E.; van Leemputte, M.; Hespel, P. (Journal of Sports Sciences, 2008)
In this study, we evaluated the effects of a novel pedal design, characterized by a downward and forward shift of the cleat fixing platform relative to the pedal axle, on maximal power output and mechanical efficiency in 22 well-trained cyclists. Maximal power output was measured during a series of short (5-s) intermittent sprints on an isokinetic cycle ergometer at cadences from 40 to 120 rev · min-1. Mechanical efficiency was evaluated during a submaximal incremental exercise test on a bicycle ergometer using continuous O2 and CO2 measurement. Similar tests with conventional pedals and the novel pedals, which were mounted on the individual racing bike of the participant, were randomized. Results: Maximal power was greater with novel pedals than with conventional pedals (between 6.0%, sx = 1.5 at 40 rev · min-1 and 1.8%, sx = 0.7 at 120 rev · min-1; P = 0.01). Torque production between crank angles of 60° and 150° was higher with novel pedals than with conventional pedals (P = 0.004). The novel pedal design did not affect whole-body O2 or CO2. Mechanical efficiency was greater with novel pedals than with conventional pedals (27.2%, sx = 0.9 and 25.1%, sx = 0.9% respectively; P = 0.047; effect size = 0.9). In conclusion, the novel pedals can increase maximal power output and mechanical efficiency in well-trained cyclists.